Impact of Globalization: An Overview of Insurance Industries in India - Vijaylakshmi, B. (Indian Journal of Finance, 2009)
In the twenty-first century, globalization has become the driver of change in the business plans of most multinational corporations. The rapid improvement in communications technology and the tendency towards more open economies have lead to the development of the globalization concept, with an assumption that the world is one big market, having access to all regions and all communities.Further the dramatic changes are taking place in international markets owing to the internationalization of activities, the appearance of new risks, new type of covers to match with new risk situations, and unconventional ideas on customer's services. Leading insurance companies are positioning themselves to succeed in future requiring significant changes in the way they do business. Despite the challenges ahead, opportunities for growth can be found by expanding globally, adopting the latest technologies to enhance service delivery and providing services to meet the needs of the customers. It also has to prepare itself to face competition in the global arena by making its operations efficient and cost effective. In the context of present scenario this paper discusses the impact of globalization on Indian insurance business, particularly on global risk exposure, global risk management and significant advantages of globalization.